“Ingroup love” and “outgroup hate” in intergroup conflict between natural groups - Weisel, Ori; Böhm, Robert (Elsevier, 2015)
We report on two studies investigating the motivations (“ingroup love” and “outgroup hate”) underlying individual participation in intergroup conflict between natural groups (fans of football clubs, supporters of political parties), by employing the Intergroup Prisoner's Dilemma Maximizing-Difference (IPD-MD) game. In this game group members can contribute to the ingroup (at a personal cost) and benefit ingroup members with or without harming members of an outgroup. Additionally, we devised a novel version of the IPD-MD in which the choice is between benefiting ingroup members with or without helping members of the outgroup. Our results show an overall reluctance to display outgroup hate by actively harming outgroup members, except when the outgroup was morality-based. More enmity between groups induced more outgroup hate only when it was operationalized as refraining from help.